Motor neuron disease: The impact of decreased speech intelligibility on marital communication - K. Joubert; J. Bornman (South African Family Practice)
Background: The onset of motor neuron disease (MND), a neurodegenerative disease, results in physical and communication disabilities that impinge on an individual’s ability to remain functionally independent. Multiple aspects of the marital relationship are affected by the continuously changing roles and responsibilities. Communication is one of the most constructive ways of dealing with emotions that are elicited by these changes.